Improvement in running time to exhaustion at 100% VO2max in recreationally active male runners with a preexercise single-carbohydrate mouth rinse - Rossato, L. T.; Fernandes, C. T. M.; Vieira, P. F.; de Branco, F. M. S.; Nahas, P. C.; Puga, G. M.; de Oliveira, E. P. (International Journal of Sports Physiology and Performance, 2019)
It is known that the reduction of muscle glycogen is not a limiting factor for performance in exercises lasting <1 hour.1 However, some studies have shown a beneficial effect on performance after carbohydrate (CHO) intake in these types of exercise,1-3 suggesting that the improvement in performance may be caused due to a CHO-induced central effect.4 It is proposed that taste cells receptors localized on buccal mucosa are activated specifically by CHO, independently of taste,5-7 and consequently, stimulate specific brain regions, such as ventral striatum, dorsolateral prefrontal cortex, and anterior cingulate cortex, which are supposedly related to form a connection between gustatory pathways and cognitive, behavioral, and emotional responses.8